Efficacy of Different Disinfectants on Isolated and Biofilmbiofilm-Associated Yeast from a Beverage Production Facility - Abdul, Roshan Aara (Central University of Technology, Free State, 2020)
In the food industry, disinfectants are routinely used to sanitize and disinfect product contact surfaces. These disinfectants provide a necessary and required step to ensure that the foods produced and consumed are as free as possible from microorganisms that can cause foodborne illness and spoilage. Disinfection is the reduction, by means of chemical agents and/or physical methods, of the number of microorganisms in the environment to a level that does not compromise food safety or suitability. Disinfection can be inadequate and cause unwanted issues such as spoilage which can result in product recalls. Factors which can cause inefficient disinfection include: incorrect dilution of chemicals, inadequate contact time, not cleaning the surface before the disinfection stage or not using a suitable disinfectant. Other factors can include and the presence of biofilms which make the process more challenging or the development of resistance to disinfectant actions. Sometimes, it is thought that microbial resistance is present when actually the organisms are avoiding contact with the disinfectant because a biofilm is present. Biofilms are polysaccharides that allow attachment to most surfaces. Over time, the film becomes enhanced and may contain different species of bacteria or yeast yielding a constant source of contamination which then reflects as ineffective disinfection is taking place. In a previous study, 20 yeast species were isolated from final concentrated beverage products and on direct food contact surfaces after the disinfection process, alluding to the fact that the disinfection process was insufficient for a processing facility producing concentrated beverages. Eight disinfectants displaying oxidative and non-oxidative modes of action with active ingredients including peracetic acid, didecyl dimethyl ammonium chloride, iodine and potassium iodide, chlorine and oxygen dissolved and volatile secondary metabolites were tested using the minimum inhibitory concentration (MIC) 96 well broth dilution laboratory protocol. The MIC was performed by five minutes contact time on the 20 yeast isolates at uniform growth numbers against the eight disinfectants, followed by incubation and visual determination of the point where inhibition stopped. The MIC results yielded two disinfectants with didecyl dimethyl ammonium chloride (DDAC2) active ingredient which displayed 100% inhibition at a maximum concentration of 0.1% usage against the 20 yeast isolates tested compared to ranges of 0% to a maximum of only 20% inhibition achieved by the remaining disinfectants. The two disinfectants, being quaternary ammonium compounds (QAC’s) which had only different concentrations of the active ingredient, were then subjected to facility trial protocols for a period of six months to determine if the action displayed in the laboratory results was also applicable on industrial scale application. The facility trial sampling focused on the direct food contact surfaces which would promote biofilm development, namely the filler line nozzles. Sampling included swabs of nozzles, before disinfectant changeover, two weeks, two months and six months after changeover respectively. Both disinfectants used during the facility trial showed positive results in terms of yeast growth reductions where one disinfectant which contained a higher concentration of DDAC2 in particular showed 94.5% reduction in number of colonies counted obtained from nozzle swabs within two months of use. Both disinfectants would also result in a significant cost saving initiative for the facility. Culturable yeast diversity changes during the trial were studied using denaturing gel electrophoresis (DGGE). DGGE results provided further information on which yeasts both or one of the disinfectants tested were able to inhibit. These included Candida sojae, Pichia occidentalis, Rhodotorula dairenensis, Sporidiobolus sp. and Rhynchogastrema noutii as well as an uncultured isolate. Lodderomyces elongisporus and Kazachstania exigua however, were not inhibited during the facility trial by both disinfectants. The industrial trial demonstrated that QAC disinfectant rather than an acid based product yielded better disinfection in the particular facility. The study identified shortcomings in protocols where an unsuitable growth medium was utilized which caused an underestimation of yeast load present in nozzles. The identification of these aspects will prove advantageous to the facility to improved monitoring protocols and provide a true representation of the yeast load in filler nozzles. In conclusion the more efficient disinfectant with capabilities to better prevent biofilm development was identified. L. elongisporus and K. exigua were however not inhibited by these disinfectants and further exposure is necessary to determine the extent of tolerance/resistance. The findings of the study will assist to prevent the occurrences of spoilage experienced by the facility resulting in reduced financial losses and brand protection and provides opportunities for further studies.
Thesis